Experimental study of the operating parameters of a photovoltaic device designed for building facades - Zukhra I. Jurayeva; Isroil A. Yuldoshev; Islom R. Jurayev (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: Renewable energy installations can reduce carbon emissions, ensure environmental safety and environmental protection. Currently, the capacities of photovoltaic and wind power plants are increasing in many countries of the world, including the Republic of Uzbekistan. Especially, due to the significant potential of solar energy in the geographical conditions of Uzbekistan, solar energy technologies are of urgent importance. For efficient and sustainable energy supply to homes and buildings, conducting research on the parameters of photovoltaic installations, depending on various factors in natural conditions, allows us to find optimal solutions for integration and adaptation to buildings. The introduction of photovoltaic technologies for energy supply to buildings will help improve energy and heat supply and increase the energy efficiency of residential and non-residential buildings. Aim: analysis of changes in the energy parameters of photovoltaic installations depending on environmental factors and the angle of inclination to the horizon of an experimental facade photovoltaic installation based on cadmium telluride in natural environmental conditions. Methods: an experimental method for studying the operation of a photovoltaic installation by measuring the main parameters. Results: An experimental facade photovoltaic installation based on a cadmium telluride thin-film panel was created. Numerous experiments were conducted, and results were obtained on the variation of the parameters of the thin-film photovoltaic system depending on the tilt angle to the horizon and environmental factors. At tilt angles of 33 and 60 degrees to the horizon, the power and temperature of photovoltaic panels increase compared to their vertical position This installation is used to conduct further research to study and improve the performance of panels in field conditions.